COMPLETE GENOME SEQUENCE OF ESCHERICHIA COLI E706 ISOLATED FROM A CHICKEN FARM - S. Zhao; G. R. Mustafa; S. Yang; W. Deng; X. Yu; L. Zou＊ (Journal of Animal and Plant Sciences, 2020)
Escherichia coli is normal gut commensal for animals as well as humans, meanwhile it can be present in the environment. Basing on whole genome sequencing (WGS), we characterized the E. coli strain E706, which harbors a series of virulence and resistance genes, CRISPR candidate elements, prophage related sequences, as well as genomic islands. The plasmid pLKJULY7989 in E706 is a chimera plasmid made up of a basic IncFIB plasmid backbone with class 1 integron and multi-resistance genes. pLKJULY7989 carries a class 1 integron with the existence of gene cassette dfrA12-aadA2 and class 1 integrase gene intl1, which is lacked in homologous plasmid pEHS30-1. The class 1 integron was detected only harboring a class 1 integrase gene, and gene cassette dfrA12-aadA2. The complete sequence we reported here will provide valuable information for a more understanding about the genomic structure and pathogenic characteristics of the genome of E. coli.
Keywords: Escherichia coli; plasmid; whole genome sequencing; resistance gene